2019
DOI: 10.1021/acs.inorgchem.9b01219
|View full text |Cite
|
Sign up to set email alerts
|

CaMn0.5Ir0.5O2.5: An Anion-Deficient Perovskite Oxide Containing Ir3+

Abstract: Reaction between CaMn0.5Ir0.5O3 and NaH, either through solid-solid contact or via a gas mediated reaction process, yields the topochemically reduced phase CaMn0.5­Ir0.5O2.5 in which Mn3+ and Ir3+ cations are located within a partially anion-vacancy disordered lattice. Magnetization data from CaMn0.5­Ir0.5O2.5 can be fit by the Curie–Weiss law to yield C = 1.586 cm3 K mol–1 and θ = −86.9 K, consistent with a combination of S = 2, Mn3+ and S = 0, Ir3+. On cooling below T ∼ 110 K, the system undergoes a transiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Later, Kobayashi et al [32] successfully conducted the reduction of SrFeO3 to SrFeO2 with physically separated CaH2, and it was concluded that the reaction was proceeded via the release of H2 by CaH2. Recently, Page et al [33] reduced CaMn0.5Ir0.5O3 using NaH and a gas mediated reaction process was proposed. Here, our results, which are identical for the physically separated and mixed experiments, once again confirms that the reduction using CaH2 works via H2 gas instead of solid state reaction.…”
Section: Synthesis Of Nd1-xsrxnio2 By Reducing Nd1-xsrxnio3mentioning
confidence: 99%
“…Later, Kobayashi et al [32] successfully conducted the reduction of SrFeO3 to SrFeO2 with physically separated CaH2, and it was concluded that the reaction was proceeded via the release of H2 by CaH2. Recently, Page et al [33] reduced CaMn0.5Ir0.5O3 using NaH and a gas mediated reaction process was proposed. Here, our results, which are identical for the physically separated and mixed experiments, once again confirms that the reduction using CaH2 works via H2 gas instead of solid state reaction.…”
Section: Synthesis Of Nd1-xsrxnio2 By Reducing Nd1-xsrxnio3mentioning
confidence: 99%
“…5 A and B ). However, one of the diagnostic features of a typical spin-glass system (low-temperature field-dependent magnetization data displaced from the origin) ( 30 ) is absent in our M vs. H plots ( Fig. 5 C and D ), which could be due to the nearly-fully-ordered character of our sample and the relatively low sensitivity of our M vs. H measurements.…”
Section: Resultsmentioning
confidence: 79%
“…This observation is consistent with a large proportion of Ir 3+ (d 6 ) with filled t 2g manifold (J eff = 3/2 and ½), corresponding to a J = 0 ground state. 64,65 .…”
Section: Resultsmentioning
confidence: 99%